Structural dynamics for engineers - Buchholdt, H. A. 1925- (ICE Pub., 2012)
This text provides practising engineers with an introduction to the dynamics of civil engineering whilst ensuring that they acquire an understanding of the theories that form the basis of computer packages.
Keywords: Structural dynamics.; elektronické knihy; electronic books